Occupational safety and health improvement at casting plant - Hussin, Norasikin (2010)
Occupational safety and health issues among workers are gaining prominence in industrial sectors. To ensure that all workers are free from any hazards, preventive actions should be given priority. These hazards can cause accidents and ill health to the workers due to unsafe conditions or unsafe act. This project was carried out at a casting plant. The project have identified the hazard, assess the risk and proposed control measures. Three methods are used to collect data which are questionnaires, interviews and observations. Process with high risk is pouring process due to manual lifting and carrying molten metal. The hot environment cause heat stress, and sand dust can cause silicosis. Trolley was designed to eliminate the need to carry the molten metal during pouring. Finite element analysis was carried out to study the strength of material and suitability of the design. A ventilation system was proposed to reduce the effect of heat stress and mineral dust from the greensand mold. Engineering analysis was carried out during the design of the ventilation system.